Residues of organochlorine pesticides and PCBs in some Brazilian municipal solid waste compost - Lourencetti, Carolina [UNESP]; Favoreto, Rodrigo [UNESP]; Marchi, Mary Rosa Rodrigues de [UNESP]; Ribeiro, Maria L. [UNESP] (Taylor & Francis, 2007)
Persistent organic pollutants (POPs), organochlorine pesticides and polychlorinated biphenyls (PCBs), listed as per the Stockholm Convention (α -HCH, β -HCH, γ -HCH, p,p′-DDT, o,p′-DDT, p,p′-DDD, p,p′-DDE, aldrin, endrin, dieldrin, PCBs 28, 52, 118, 138, 153, and 180), were analyzed in municipal solid waste (MSW) compost samples from three different Brazilian composting plants located in three São Paulo State cities: Araras, Araraquara and São Paulo (Vila Leopoldinha). Quantitative and qualitative analyses were carried out using gas chromatography electron capture detection (GC-ECD) and gas chromatography mass spectrometry (GC-MS) (Ion Trap, electron impact ionization), respectively. The samples were analyzed in triplicate and the target POPs were not detected by GC-ECD. Twelve pollutants were identified in two samples when qualitative analysis (GC-MS) was used (β -HCH, γ -HCH, p,p′-DDT, o,p′-DDT, p,p′-DDD, and p,p′-DDE, PCBs 28, 118, 138, 153 and 180). The composting process has advantages such as urban solid waste reduction and landfill life-span increase, however the MSW compost quality, which can be utilized for agricultural purposes, should be evaluated and be controlled. This kind of study is the first step in making available information to answer questions regarding MSW compost for sustainable agricultural use, such as the pollutants accumulation in soil and in groundwater, and plants uptake. Copyright © Taylor & Francis Group, LLC.
Keywords: Gas chromatography; Municipal solid waste; Organochlorine pesticides; Persistent organic pollutants; Polychlorinated biphenyls; Chlorine compounds; Composting; Solid wastes; Municipal solid wastes (MSW); Persistent organic pollutants (POP); Polychlorinated biphenyls (PCB); Pesticides; chlorinated hydrocarbon; pesticide; pesticide residue; polychlorinated biphenyl; compost; gas chromatography; landfill; municipal solid waste; organochlorine; PCB; Stockholm Convention; Brazil; environmental monitoring; mass fragmentography; methodology; pollutant; pollution; Chromatography, Gas; Environmental Monitoring; Environmental Pollutants; Gas Chromatography-Mass Spectrometry; Hydrocarbons, Chlorinated; Pesticide Residues; Polychlorinated Biphenyls; Waste Products